Emerging Centers in the Northeastern Middle Atlas: Balancing Spatial Organization and Achieving Sustainable Development - The Case of Zararda Center - Mohammed, Goumihi; El-Bazoui, Jaouad; Bouberria, Abdelouahed (Journal of Humanities & Social Sciences, 2024)
The spatial and territorial transformations experienced by the Moroccan territory have led to the emergence of new spatial entities known as emerging and rising centers. These centers have become a strategic tool in restructuring Moroccan space and a means to create territorial balance by spreading urbanization to new areas. They have also facilitated population stability within these areas, helping to reduce pressure on traditional urban spaces. The northeastern Middle Atlas Mountains have witnessed significant territorial transformations, with the emergence of several nascent centers. These centers have transitioned from simple rural gatherings to self-sustaining centers equipped with numerous important facilities and infrastructure. This development has aided in organizing their rural space and in attracting various surrounding territorial components. In this academic paper, we aim to shed light on the current state of the Zararda Center, an emerging entity in the northeastern Middle Atlas, and propose key approaches to achieving sustainable development within this territorial area.